# If x5.y7 = (x + y)12, then show that dydx=yx - Mathematics and Statistics

Sum

If x5.y7 = (x + y)12, then show that ("d"y)/("d"x) = y/x

#### Solution

x5.y7 = (x + y)12

Taking logarithm of both sides, we get

log(x5.y7) = log(x + y)12

∴ log x5 + log y7 = 12 log (x + y)

∴ 5 log x + 7 log y = 12 log (x + y)

Differentiating both sides w.r.t. x, we get

5*1/x + 7*1/y*("d"y)/("d"x) = 12*1/(x + y)*"d"/("d"x)(x + y)

∴ 5/x + 7/y*("d"y)/("d"x) = 12/(x + y)(1 + ("d"y)/("d"x))

∴ 5/x + 7/y*("d"y)/("d"x) = 12/(x + y) + 12/(x + y)*("d"y)/("d"x)

∴ 7/y*("d"y)/("d"x) - 12/(x + y)*("d"y)/("d"x) = 12/(x + y) - 5/x

∴ (7/y - 12/(x + y)) ("d"y)/("d"x) = 12/(x + y) - 5/x

∴ [(7x + 7y - 12y)/(y(x + y))]("d"y)/("d"x) = (12x - 5x - 5y)/(x(x + y))

∴ [(7x - 5y)/(y(x + y))] ("d"y)/("d"x) = [(7x - 5y)/(x(x + y))]

∴ ("d"y)/("d"x) = (7x - 5y)/(x(x + y)) xx (y(x + y))/(7x - 5y)

∴ ("d"y)/("d"x) = y/x

Concept: The Concept of Derivative - Derivatives of Logarithmic Functions
Is there an error in this question or solution?